Towards inconspicuous security - Goh, Weihan (2013)
This dissertation presents novel ideas on the design and analysis of techniques to provide security while being minimally conspicuous. The author identifies three key areas in which such techniques can be used, and evaluates the performance of the techniques when used. The three areas identified are the areas of information anti-forensics, mobile system anti-forensics, and threat mitigation in disruption tolerant networks. Additionally, the author proposes a technique to utilize a Trusted Platform Module to enhance the security of the key generating authority in a Shamir identity-based signature scheme.